Race and Human Capital: Reply - Smith, James P. (American Economic Review, 2016)
To arrive at a tenable interpretation of black history, it is important to resolve the conflict between my measure-retrospective years of schooling completed-and Robert Margo's measure-prospective accumulation across ages of cohort-specific attendance rates. My series reconciled the apparent inconsistency between the stagnant pre-1940 black-white income ratios and what scholars had previously thought was a steady narrowing of racial education differences. Margo's series not only would restore that incon